A Comparison of Segregated and Integrated Infant and Toddler Programs in One Childcare Centre. Issue 2 (June 2013) - Rutherford, Lynne; Whitington, Victoria
TO CREATE AN ENVIRONMENT more conducive to the needs of very young children from January 2011, Gowrie SA replaced age groupings, which separated infants and toddlers with integrated infant–toddler programs. The aim of this study was to evaluate this program change by comparing the two types of infant and toddler programs, before and after implementation. The evaluation focused on those areas considered to have most impact on children's development (Ackerman, 2008): the overall length of time educators and children spend together, the depth of documentation and assessment of children's learning as evident in learning stories, and the quality of interactions between educators and families during drop-off and pick-up times. Statistically significant differences were found for the first two areas and higher frequencies in the third area, showing overall improvement under the integrated program. Parents' and educators' perceptions about the advantages and challenges of integrated infant–toddler programs were also included in the study.